TEOLOGI PRIBUMI DI INDONESIA - Karman, Yonky (STT Amanat Agung, 2022)
Abstract: One of the problems with the indigenization of Christian theology in Indonesia is how to respond positively to the Indonesian context. This problem is inseparable from Indonesian theologies which in many respects depend on the final product of Western theologies, a dependence on doing theology without independence and creativity. To overcome this dependence and at the same time foster theological independence, it is first important to reposition the passive subject of doing theology into an active subject by adopting a cultural approach (constructive orientalism). Second, getting rid of the tendency to disbelieve in local elements by reviewing the